Information quality and students’ academic performance: the mediating roles of perceived usefulness, entertainment and social media usage - Abdallah M. M. Badr; Badr Saleh Al-Abdi; Maged Rfeqallah; Rozilah Kasim; Faisal A. M. Ali (Smart Learning Environments)
Abstract Purpose This study evaluates the mediating roles of entertainment, perceived usefulness, and social media use on social information (content) and students’ academic performance. Methodology Primary data was collected from 445 students at King Khalid University in Saudi Arabia using the snowball sampling strategy was employed. For data analysis, structural equation modeling (PLS-SEM) was used. Findings Entertainment partly mediates the link between social information quality “content” (IQ) and social media use (SMU) and SMU mediates the link between IQ and student’s academic performance (SAP). Perceived usefulness mediates the link between IQ and SAP. Suggesting that entertainment and perceived usefulness are crucially necessary for inspiring social media content to obtain optimum performance among graduate students. The study was limited to a single academic institution. Therefore, the results of the investigation cannot be generalized as a whole, and cannot track respondents’ social media activity over time. Thus, longitudinal data may be used in future investigations. Practical implications The results of this study indicate that faculties can adapt and adjust their teaching methods and activities to incorporate social media, perceived usefulness, and entertaining content since it affects student performance. Social media (SM) has a significant influence on students’ social and academic performance. Thus, educational stakeholders, such as university authorities, the government, and parents and guardians, should recognize social media as a tool for achieving educational objectives. Originality/value The study enhances the application of UTAUT2 by examining how factors that influence the adoption of technology are connected to the subsequent influence of that adoption on students’ learning and conduct.